A Kinetic Model Explains Why Shorter and Less Affine Enzyme-recruiting Oligonucleotides Can Be More Potent - Lykke Pedersen; Peter H Hagedorn; Marie Wickström Lindholm; Morten Lindow (Elsevier, 2014)
Antisense oligonucleotides complementary to RNA targets promise generality and ease of drug design. The first systemically administered antisense drug was recently approved for treatment and others are in clinical development. Chemical modifications that increase the hybridization affinity of oligonucleotides are reasoned to confer higher potency, i.e., modified oligonucleotides can be dosed at lower concentrations to achieve the same effect. Surprisingly, shorter and less affine oligonucleotides sometimes display increased potency. To explain this apparent contradiction, increased uptake or decreased propensity to form structures have been suggested as possible mechanisms. Here, we provide an alternative explanation that invokes only the kinetics behind oligonucleotide-mediated cleavage of RNA targets. A model based on the law of mass action predicts, and experiments support, the existence of an optimal binding affinity. Exaggerated affinity, and not length per se, is detrimental to potency. This finding clarifies how to optimally apply high-affinity modifications in the discovery of potent antisense oligonucleotide drugs.